Application of Failure Mode and Effect Analysis (FMEA) for Defect Reduction: A Case Study on Scratch Defects in Oil Separator Parts in Machining Line - Sumasto, Fredy; Christiani, Jean; Wulansari, Isma; Rozi, Muhamad Fahrul; Dzulfikar, Arif; Ismono, Ahlan (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
This study addresses the problem of significant defect rates on Oil Separator Parts in machining line, especially focusing on scratch defects. The defect rate reached 0.495%, exceeding the company’s target of 0.1%. In the approach using FMEA, potential failure modes were identified and rated based on Risk Priority Number to plan corrective actions. Effort and Impact Analysis was used to analyze the most effective action recommendations. Implementation of the 5S methodology was selected as the improvement solution, which focused on workplace organization, maintenance, and cleanliness. The results were positive, with the number of defects decreasing dramatically from 540 to 67 units in July 2023, and the defect rate dropping from 0.495% to 0.145%. Although the company’s quality targets have not been fully achieved, the FMEA approach and 5S implementation have been shown to significantly improve production quality and reduce defects. This study proves that this approach has the potential to address complex quality issues, although further challenges may be required to achieve the final goals set.